Composite material as well as preparation method and application thereof

By combining the multi-arm amphiphilic block copolymer with inorganic minerals to form a composite material with dendritic structure, the problem of insufficient processability, toughness and modifiability of linear polymers in bone tissue regeneration and repair is solved, and better bone tissue repair effect is achieved.

CN119868645APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311389137.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the processability, toughness and modifiability of linear polymers are insufficient, resulting in limited application of their bone tissue regeneration and repair.

Method used

Multi-arm amphiphilic block copolymer is used to recombinate with inorganic minerals, and the dendritic structure is formed through polymerization reaction, which improves interaction with inorganic minerals, enhances cell growth, proliferation and differentiation capabilities, and achieves controllable performance of composite materials through specific molar ratios.

Benefits of technology

It improves the melt strength and toughness of composite materials, enhances its interaction with inorganic minerals, promotes cell growth and bone tissue repair, and meets the needs of bone tissue repair in different parts of the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868645A_ABST
    Figure CN119868645A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological materials, and discloses a composite material as well as a preparation method and application thereof. The composite material comprises a multi-arm amphiphilic block copolymer and an inorganic mineral substance, the multi-arm amphiphilic block copolymer is a dendritic copolymer which takes a hydrophilic multi-arm polyethylene glycol chain segment as a core and is connected with a lipophilic polyester chain segment at the tail end; the molar ratio of the hydrophilic multi-arm polyethylene glycol chain segment to the lipophilic polyester chain segment is 1: (3-12). The multi-arm amphiphilic block copolymer with the structure can improve the interaction with inorganic mineral substances and help cell growth, proliferation and differentiation; and the hydrophilic multi-arm polyethylene glycol chain segment and the lipophilic polyester chain segment have a specific molar ratio, so that the performance of the composite material can be controlled, and the requirements of bone tissue repair of different parts of a human body can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] As the world's population ages, bone-related diseases have become a major chronic condition in humans. In particular, critical bone tissue defects caused by trauma, tumor resection and infection pose a particularly serious threat to human health. Therefore, effectively repairing bone loss and restoring the physiological function of bone tissue has become a hot topic in the current biomedical field. Autologous bone transplantation and allogeneic bone transplantation are commonly used methods for regenerating and repairing defective bone tissue in clinical practice, but these methods are limited by the limited amount of viable bone tissue and the risk of disease transmission caused by incomplete devitalization. The emergence of scaffold-guided bone tissue regeneration technology provides a powerful way to address these challenges. Inorganic materials such as bioactive glass, hydroxyapatite, and β-calcium phosphate have excellent biological activity, can promote the formation of bone tissue, and are one of the commonly used bone tissue regeneration and repair materials. However, inorganic materials are not easy to process and shape, and clinical operations are inconvenient, making them unsuitable for repairing larger bone defects. Degradable natural polymers such as collagen, gelatin, chitosan, etc. have attracted wide attention due to their advantages such as good processability, excellent biocompatibility, and convenience for surgical operation. However, these polymers usually have low mechanical strength and weak self-induction bone formation ability. They often need to add a large amount of growth factors to promote the regeneration and repair of bone damage, which increases costs and even causes serious side effects. Synthetic degradable polymers such as polylactic acid (PLA), polyglycolic acid (PGA), and polycaprolactone (PCL) have moderate mechanical properties, adjustable degradation rates, excellent processing properties, large-scale production, and low costs. They have great potential in bone tissue regeneration and repair. However, due to the hydrophobicity of this type of polyester polymer, its effect on repairing bone damage is not ideal. Professor Jie Song of the University of Massachusetts Medical School introduced hydrophilic polyethylene glycol (PEG) segments into PLA to form a triblock amphiphilic copolymer PELA, which was then composited with hydroxyapatite and prepared into a three-dimensional porous scaffold by 3D printing, achieving excellent bone tissue repair effects. However, the poor melt strength of linear polylactic acid itself limits its processing performance to a large extent, and the conditions required for 3D printing are relatively harsh. In addition, linear polylactic acid materials generally have poor flexibility, resulting in brittle scaffolds. At the same time, linear polymers have limited end groups and insufficient modifiability, which limits the application range of the material. Summary of the invention

[0003] The purpose of the present invention is to overcome the problem that the linear polymer in the prior art is insufficient in processability, toughness and modifiability, resulting in limited application, and to provide a composite material and a preparation method and application thereof. The composite material comprises a multi-arm amphiphilic block copolymer and an inorganic mineral. The multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as a core and a lipophilic polyester segment connected to the end. The multi-arm amphiphilic block copolymer with the above structure can improve the interaction with the inorganic mineral and help cell growth, proliferation and differentiation; and the hydrophilic multi-arm polyethylene glycol segment and the lipophilic polyester segment have a specific molar ratio, which can realize controllable performance of the composite material to meet the needs of bone tissue repair in different parts of the human body.

[0004] In order to achieve the above object, the present invention provides a composite material in a first aspect, characterized in that the composite material comprises a multi-arm amphiphilic block copolymer and an inorganic mineral;

[0005] Wherein, the multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as the core and a lipophilic polyester segment connected at the end;

[0006] The molar ratio of the hydrophilic multi-arm polyethylene glycol segment to the lipophilic polyester segment is 1:3-12;

[0007] The hydrophilic multi-arm polyethylene glycol chain segment comes from hydrophilic multi-arm polyethylene glycol, and the number of arms of the hydrophilic multi-arm polyethylene glycol is 3-12.

[0008] A second aspect of the present invention provides a method for preparing a composite material, characterized in that the method comprises the following steps:

[0009] S1. In the presence of a catalyst, a hydrophilic multi-arm polyethylene glycol and a lipophilic polyester monomer are mixed to carry out a polymerization reaction to obtain a multi-arm amphiphilic block copolymer;

[0010] S2, mixing and shaping the multi-arm amphiphilic block copolymer and the inorganic mineral to obtain the composite material;

[0011] Wherein, the molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:160-10000.

[0012] The third aspect of the present invention provides a composite material prepared by the method described in the second aspect.

[0013] The fourth aspect of the present invention provides a use of the composite material described in the first aspect or the third aspect in bone tissue repair.

[0014] Through the above technical solution, the composite material provided by the present invention and its preparation method and application obtain the following beneficial effects:

[0015] (1) Based on the molecular topology, the present invention grafts hydrophilic multi-arm polyethylene glycol segments onto lipophilic polyester segments to form multi-arm amphiphilic block copolymers without changing the polymer composition and molecular weight, which can enhance the interaction with inorganic minerals, help cell growth, proliferation and differentiation, and be better applied to bone tissue repair;

[0016] (2) The multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as the core and a lipophilic polyester segment connected at the end, which has good melt strength, so that the composite material has better processing performance and enhances the toughness of the multi-arm amphiphilic block copolymer;

[0017] (3) The hydrophilic multi-arm polyethylene glycol chain segment and the lipophilic polyester chain segment have a specific molar ratio, which can achieve controllable performance of the composite material to meet the needs of bone tissue repair in different parts of the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the process of preparing the composite material according to the present invention. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a composite material, characterized in that the composite material comprises a multi-arm amphiphilic block copolymer and an inorganic mineral;

[0021] Wherein, the multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as the core and a lipophilic polyester segment connected at the end;

[0022] The molar ratio of the hydrophilic multi-arm polyethylene glycol chain segment to the lipophilic polyester chain segment is 1:3-12.

[0023] In the present invention, the multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as the core and a lipophilic polyester segment connected to the end. The multi-arm amphiphilic block copolymer with the above structure can improve the interaction with inorganic minerals and help cell growth, proliferation and differentiation; the dendritic copolymer has modifiability and good toughness; the hydrophilic multi-arm polyethylene glycol segment and the lipophilic polyester segment have a specific molar ratio, which can achieve controllable performance of the composite material to meet the needs of bone tissue repair in different parts of the human body.

[0024] According to the present invention, the composite material comprises 30 wt% to 95 wt% of a multi-arm amphiphilic block copolymer and 5 wt% to 70 wt% of an inorganic mineral.

[0025] In the present invention, the contents of the multi-arm amphiphilic block copolymer and the inorganic mineral satisfy the above ranges, and can have an excellent bone tissue repairing effect.

[0026] Furthermore, the composite material comprises 50 wt% to 90 wt% of the multi-arm amphiphilic block copolymer and 10 wt% to 50 wt% of the inorganic mineral.

[0027] According to a preferred embodiment of the present invention, the molar ratio of the hydrophilic multi-arm polyethylene glycol segment to the lipophilic polyester segment is 1:4-8.

[0028] According to the present invention, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

[0029] According to a preferred embodiment of the present invention, the number of arms of the hydrophilic multi-arm polyethylene glycol is 4-8.

[0030] In the present invention, the number of arms of the hydrophilic multi-arm polyethylene glycol satisfies the above range, which can ensure the efficiency of the polymerization reaction.

[0031] According to the present invention, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol is 2000-200000 g / mol, preferably 10000-50000 g / mol.

[0032] According to the present invention, the lipophilic polyester chain segment is derived from a lipophilic polyester monomer.

[0033] According to the present invention, the lipophilic polyester monomer is lactide.

[0034] According to the present invention, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol segment is 2000-200000 g / mol, preferably 10000-50000 g / mol.

[0035] According to the present invention, the number average molecular weight of the lipophilic polyester segment is 10,000-1,000,000 g / mol, preferably 90,000-250,000 g / mol.

[0036] According to the present invention, the number average molecular weight of the multi-arm amphiphilic block copolymer is 12000-1200000 g / mol.

[0037] In the present invention, the number average molecular weight of the multi-arm amphiphilic block copolymer meets the above range and can match the mechanical properties of bone tissue.

[0038] Furthermore, the number average molecular weight of the multi-arm amphiphilic block copolymer is 100,000-300,000 g / mol.

[0039] According to the present invention, the melt index of the multi-arm amphiphilic block copolymer at 190° C. and a load of 2.16 kg is 1-50 g / 10 min, preferably 5-30 g / 10 min.

[0040] According to the present invention, the average pore size of the composite material is 200-800 μm, and the porosity is ≥40%.

[0041] A second aspect of the present invention provides a method for preparing a composite material, characterized in that the method comprises the following steps:

[0042] S1. In the presence of a catalyst, a hydrophilic multi-arm polyethylene glycol and a lipophilic polyester monomer are mixed to carry out a polymerization reaction to obtain a multi-arm amphiphilic block copolymer;

[0043] S2, mixing and shaping the multi-arm amphiphilic block copolymer and the inorganic mineral to obtain the composite material;

[0044] Wherein, the molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:160-10000.

[0045] In the present invention, the polymerization reaction is carried out under a protective atmosphere, and the protective atmosphere can be nitrogen or an inert gas.

[0046] According to the present invention, the molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:200-2000.

[0047] According to the present invention, the catalyst is selected from at least one of stannous isooctanoate, bis(N,N-bis(trimethylsilyl)amino)zinc, stannous octoate, tributylaluminum and diethylzinc.

[0048] In the present invention, the catalyst needs to be first configured as a toluene solution when used so as to be better added to the system. In addition, the hydrophilic multi-arm polyethylene glycol needs to remove water and impurities before use, which can be done according to the following method: first dissolve the catalyst in toluene, then add the solution to the multi-arm polyethylene glycol, and heat it at 120-140° C. in vacuum for 10-30 minutes to volatilize the toluene and remove a small amount of water and impurities therein.

[0049] According to the present invention, the amount of the catalyst used is 0.1wt%-1wt% of the hydrophilic multi-arm polyethylene glycol.

[0050] In the present invention, the amount of the catalyst used satisfies the above range, which can ensure that the catalyst has a certain catalytic performance and reaches the metal content standard of the medical-grade catalyst.

[0051] Furthermore, the amount of the catalyst used is 0.2wt%-0.6wt% of the hydrophilic multi-arm polyethylene glycol.

[0052] According to the present invention, the conditions of the polymerization reaction include: reaction temperature of 100-200° C., preferably 120-160° C.; reaction time of 3-6 h, preferably 4-5 h.

[0053] According to the present invention, the number of arms of the hydrophilic multi-arm polyethylene glycol is 3-12.

[0054] In the present invention, the number of arms of the hydrophilic multi-arm polyethylene glycol satisfies the above range, which can further improve the modulus and melt strength of the prepared composite material.

[0055] Furthermore, the number of arms of the hydrophilic multi-arm polyethylene glycol is 4-8.

[0056] According to the present invention, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol is 2000-200000 g / mol, preferably 10000-50000 g / mol.

[0057] According to the present invention, the lipophilic polyester monomer is lactide.

[0058] According to the present invention, in step S1, the catalyst content in the multi-arm amphiphilic block copolymer is no more than 150 ppm calculated as metal.

[0059] In the present invention, in order to make the catalyst content in the multi-arm amphiphilic block copolymer meet the above range so as to be better applied to bone tissue repair, the method further comprises purifying the multi-arm amphiphilic block copolymer obtained in step S1.

[0060] In the present invention, the purification step can adopt conventional methods in the art. For example, the purification method of the present invention is: adding chloroform to the multi-arm amphiphilic block copolymer obtained in step S1 to dissolve overnight to obtain a polymer solution. The polymer solution is added dropwise to ether to precipitate a solid, the solid is taken out, and the purified multi-arm amphiphilic block copolymer is obtained after vacuum drying.

[0061] Furthermore, in step S1, the catalyst content in the multi-arm amphiphilic block copolymer is 50-150 ppm in terms of metal.

[0062] According to the present invention, based on the weight of the composite material, the mass fraction of the inorganic mineral is 5wt%-70wt%, preferably 10wt%-50wt%.

[0063] According to the present invention, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate.

[0064] According to the present invention, the forming method is electrospinning and / or 3D printing.

[0065] In the present invention, the forming mode of electrostatic spinning is exemplarily described. Wherein, the method of electrostatic spinning is: the mixture obtained by mixing the multi-arm amphiphilic block copolymer with the inorganic mineral is added to a syringe (for example, a needle can be 22G), an aluminum disk is placed at 10-20cm below the needle, and 10-25kV high voltage is applied between the aluminum disk and the needle. The mixture is extruded at a rate of 0.5-1.5mL / h, and to ensure that the support is uniform, the aluminum disk is rotated at a certain angle (45-90 °) every 10-15min during the process. The obtained multi-arm amphiphilic block copolymer support is dried in a vacuum oven for standby use.

[0066] In the present invention, the inner diameter of the needle, the distance between the needle and the aluminum disk, the pressure between the aluminum disk and the needle, the extrusion rate of the mixture, and the rotation angle and method of the aluminum disk are all conventional methods. The above data are only illustrative of the operation and are not intended to limit it.

[0067] Further, the 3D printing method is illustratively as follows: the mixture obtained by mixing the multi-arm amphiphilic block copolymer and the inorganic mineral is poured into a Teflon mold, placed in a fume hood for 12 hours, and then completely dried in an oven and cut into small pieces. The mixture cut into small pieces is made into filaments using a capillary rheometer, and the filaments are printed into a composite material of a desired size using a 3D printer.

[0068] In the present invention, the placement time after the mixture is poured into the Teflon mold, the size of the small pieces, the size of the filaments, and the size of the composite material are only exemplary for the operation and are not intended to limit the same.

[0069] In the present invention, illustratively, the conditions for 3D printing are set as follows: line spacing of 0.6-1 mm, ambient temperature of 3-5° C., printing speed of 80-100 mm / s, nozzle temperature of 150-180° C., and platform temperature of 20-50° C.

[0070] In the present invention, before mixing the multi-arm amphiphilic block copolymer with the inorganic mineral, the inorganic mineral is preferably dispersed in an organic solvent and ultrasonically mixed, and then the multi-arm amphiphilic block copolymer is added and stirred to obtain a mixture. The organic solvent is chloroform or a mixed solvent of chloroform / dimethylformamide, wherein the mass ratio of chloroform to dimethylformamide is 1-4:1.

[0071] In the present invention, the ultrasonic conditions are not particularly limited, as long as the inorganic minerals can be evenly dispersed in the organic solvent. Similarly, the stirring conditions after adding the multi-arm amphiphilic block copolymer are not particularly limited, for example, stirring can be performed at room temperature for 12 hours.

[0072] according to Figure 1 A specific embodiment of the present invention is described, wherein the method comprises the following steps:

[0073] S1. Heating a hydrophilic multi-arm polyethylene glycol (PEG) at 100-150° C. under vacuum for 1-3 h to remove water and impurities, and polymerizing the PEG and a lipophilic polyester monomer at 100-200° C. for 4-5 h in the presence of a catalyst to obtain a multi-arm amphiphilic block copolymer;

[0074] S2, adding chloroform to the multi-arm amphiphilic block copolymer to dissolve overnight to obtain a polymer solution, adding the polymer solution dropwise into diethyl ether to precipitate a solid, and vacuum drying the solid to obtain a purified multi-arm amphiphilic block copolymer;

[0075] S3, dissolving the inorganic mineral in chloroform or a mixed solvent of chloroform / dimethylformamide, adding the purified multi-arm amphiphilic block copolymer after ultrasonic treatment for 20-40 minutes, stirring evenly at room temperature, and processing and molding to obtain a composite material;

[0076] Wherein, the molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:160-10000.

[0077] The third aspect of the present invention provides a composite material prepared by the method described in the second aspect.

[0078] In the present invention, the product has the appearance of a white or light yellow solid.

[0079] The fourth aspect of the present invention provides a use of the composite material described in the first aspect or the third aspect in bone tissue repair.

[0080] The present invention will be described in detail below through examples. In the following examples, the modulus of the composite material is measured by a dynamic thermomechanical analysis method;

[0081] Melt strength is measured by melt strength tester method;

[0082] The degradation time was measured by the following method: the prepared sample was placed in a cell culture medium and then placed on a shaker and observed every 7 days. When the sample was completely dissolved, the time taken was the degradation time;

[0083] PEG, purchased from Sigma-Aldrich;

[0084] Unless otherwise specified, the number average molecular weight of PEG involved in the examples and comparative examples is 20,000;

[0085] L-lactide, purchased from Sigma-Aldrich;

[0086] Diethylzinc, purchased from Sigma-Aldrich;

[0087] Stannous isooctanoate, purchased from Sigma-Aldrich;

[0088] Hydroxyapatite was purchased from Sigma-Aldrich.

[0089] Example 1

[0090] S1. Add 1 g of hydrophilic four-arm polyethylene glycol (PEG) to the reaction bottle, heat at 100 °C under vacuum for 2 h to remove water and impurities, and then heat at N 2 In the atmosphere, 0.05 mL of stannous isooctanoate toluene solution (100 mg / mL) was added to the reaction bottle (the effective mass of the catalyst was 5 mg), and heated at 100 ° C under vacuum conditions for 15 min to remove toluene and impurities;

[0091] In N 2 In the atmosphere, 4.375 g of L-lactide was added into the reaction bottle, and the polymerization reaction was carried out at 130° C. for 4 h under stirring to obtain a crude four-arm amphiphilic block copolymer;

[0092] S2, adding the crude four-arm amphiphilic block copolymer to 25 mL of chloroform to dissolve overnight to obtain a polymer solution, adding the polymer solution dropwise to 250 mL of ether, and precipitating a solid, and vacuum drying the solid at 60° C. to obtain a purified four-arm amphiphilic block copolymer;

[0093] S3. Dissolve 0.82g of hydroxyapatite in 5mL of chloroform and ultrasonicate for 30min, add 2.5g of purified four-arm amphiphilic block copolymer, mix well and stir for 12h. Pour the mixture into a Teflon mold and place it in a fume hood for 12h to evaporate the solvent. After the mixture is completely dried in an oven at 60℃, cut into small pieces and extruded from a 1.75mm hole at 160℃ through a capillary rheometer to obtain filaments. The filaments are printed into a 10mm×10mm×4mm composite material using a 3D printer. (The cross section of the printed line is set to 0.4mm×0.4mm, and the line spacing is 0.8mm), the ambient temperature is 4℃, the printing speed is 90mm / s, the nozzle temperature is 160℃, and the platform temperature is 30℃.

[0094] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0095] Example 2

[0096] S1. Add 2 g of hydrophilic four-arm polyethylene glycol (PEG) to the reaction bottle, heat at 100 °C under vacuum for 2 h to remove water and impurities, and then heat at N 2 In the atmosphere, 0.1 mL of diethyl zinc toluene solution (100 mg / mL) was added to the reaction bottle (the effective mass of the catalyst was 10 mg), and heated at 100 °C under vacuum for 15 min to remove toluene and impurities;

[0097] In N 2 In the atmosphere, 8.75 g of lactide was added into the reaction bottle, and the polymerization reaction was carried out at 130° C. for 5 h under stirring to obtain a crude four-arm amphiphilic block copolymer;

[0098] S2, adding the crude four-arm amphiphilic block copolymer to 50 mL of chloroform to dissolve overnight to obtain a polymer solution, adding the polymer solution dropwise to 500 mL of ether, and precipitating a solid, and vacuum drying the solid at 60° C. to obtain a purified four-arm amphiphilic block copolymer;

[0099] S3, 0.41g hydroxyapatite was dissolved in 50mL 1:4 (v / v) dimethylformamide / chloroform mixed solvent and ultrasonicated for 30min, 1.25g purified four-arm amphiphilic block copolymer was added, mixed evenly and stirred for 12h, loaded into a 5mL syringe (needle was 22G), an aluminum plate was placed 15cm below, and 12kV high voltage was applied between the aluminum plate and the needle. The mixed solution was extruded at a speed of 0.7mL / h, and the aluminum plate was rotated 90° every 15min during the process to ensure uniform composite material.

[0100] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0101] Example 3

[0102] S1. Add 1 g of hydrophilic four-arm polyethylene glycol (PEG) to the reaction bottle, heat at 100 °C under vacuum for 2 h to remove water and impurities, and then heat at N 2 In the atmosphere, 0.05 mL of stannous isooctanoate toluene solution (100 mg / mL) was added to the reaction bottle (the effective mass of the catalyst was 5 mg), and heated at 100 ° C under vacuum conditions for 15 min to remove toluene and impurities;

[0103] In N 2 In the atmosphere, 8.75 g of L-lactide was added into the reaction bottle, and the polymerization reaction was carried out at 130° C. for 4 h under stirring to obtain a crude four-arm amphiphilic block copolymer;

[0104] S2, adding the crude four-arm amphiphilic block copolymer to 50 mL of chloroform to dissolve overnight to obtain a polymer solution, adding the polymer solution dropwise to 500 mL of ether, and precipitating a solid, and vacuum drying the solid at 60° C. to obtain a purified four-arm amphiphilic block copolymer;

[0105] S3. Dissolve 3.3g of calcium phosphate in 20mL of chloroform and ultrasonicate for 30min, add 10g of purified four-arm amphiphilic block copolymer, mix well and stir for 12h. Pour the mixture into a Teflon mold and place it in a fume hood for 12h to allow the solvent to evaporate. After completely drying the mixture in an oven at 60°C, cut it into small pieces and extrude it from a 1.75mm hole at 160°C using a capillary rheometer to obtain filaments. Print the filaments into a 10mm×10mm×4mm composite material using a 3D printer. (Printing conditions are the same as in Example 1)

[0106] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0107] Example 4

[0108] The method of Example 1 was followed, except that the hydrophilic four-arm polyethylene glycol was replaced with an equimolar amount of hydrophilic three-arm polyethylene glycol. The results are shown in Table 1.

[0109] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0110] Example 5

[0111] The method of Example 1 is followed, except that the number average molecular weight of the hydrophilic four-arm polyethylene glycol is 100,000.

[0112] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0113] Example 6

[0114] The method of Example 1 is followed, except that the amount of hydroxyapatite used is 0.25 g, so that the mass fraction of the inorganic mineral is 9 wt %.

[0115] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0116] Comparative Example 1

[0117] The method of Example 1 is followed, except that the amount of hydrophilic four-arm polyethylene glycol used is 13.5 g, so that the molar ratio of the hydrophilic four-arm polyethylene glycol to the L-lactide monomer is 1:45.

[0118] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0119] Comparative Example 2

[0120] The method of Example 1 was followed, except that the hydrophilic four-arm polyethylene glycol was replaced with an equimolar amount of hydrophilic linear polyethylene glycol (the number of arms was 2).

[0121] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0122] Comparative Example 3

[0123] The method of Example 1 is followed, except that the amount of hydrophilic four-arm polyethylene glycol used is 4.05 g, so that the molar ratio of the hydrophilic four-arm polyethylene glycol to the L-lactide monomer is 1:150.

[0124] Among them, the molar ratio of hydrophilic PEG segments and lipophilic polyester segments, the number of PEG arms, the content of block copolymers, the content of inorganic minerals, the melt index and the average pore size are shown in Table 1; the number average molecular weight of PEG, the number average molecular weight of PEG segments, the number average molecular weight of polyester segments and the number average molecular weight of multi-arm amphiphilic block copolymers are shown in Table 1 (continued); the molar ratio of PEG and polyester monomers, the amount of catalyst relative to PEG, the content of catalyst in the crude amphiphilic block copolymer and the amount of inorganic minerals added are shown in Table 2.

[0125] Table 1

[0126]

[0127] PEG:Polyester a : refers to the molar ratio of hydrophilic PEG segments to lipophilic polyester segments

[0128] Table 1 (continued)

[0129]

[0130] Table 2

[0131]

[0132]

[0133] PEG:Polyester b : refers to the molar ratio of hydrophilic PEG and lipophilic polyester monomers

[0134] Test Case

[0135] The composite materials prepared in the examples and comparative examples were tested for modulus, melt strength and performance. The results are shown in Table 3.

[0136] Table 3

[0137] Compression modulus (kPa) Melt strength (mN) Degradation time (weeks) Example 1 280 20 16 Example 2 300 20 18 Example 3 410 29 22 Example 4 200 15 16 Example 5 260 18 15 Example 6 250 18 16 Comparative Example 1 30 2 6 Comparative Example 2 120 11 13 Comparative Example 3 90 5 12

[0138] From the above results, it can be seen that Examples 1-6 using the four-arm lactic acid block copolymer of the present invention have higher number average molecular weight, compression modulus and melt strength, wherein the compression modulus is not less than 200 kPa, the melt strength is not less than 15 mN, and the catalyst content is less than 100 ppm.

[0139] Comparative Examples 1 and 3 both have too large or too small molar ratios of hydrophilic PEG and lipophilic polyester monomers, which results in reduced strength and cannot be well applied to bone tissue repair. Comparative Example 2 also cannot be well applied to bone tissue repair due to the low mechanical strength of linear polyethylene glycol (arm number 2).

[0140] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite material, characterized in that: The composite material comprises a multi-arm amphiphilic block copolymer and an inorganic mineral; Wherein, the multi-arm amphiphilic block copolymer is a dendritic copolymer with a hydrophilic multi-arm polyethylene glycol segment as the core and a lipophilic polyester segment connected at the end; The molar ratio of the hydrophilic multi-arm polyethylene glycol segment to the lipophilic polyester segment is 1:3-12; The hydrophilic multi-arm polyethylene glycol chain segment comes from hydrophilic multi-arm polyethylene glycol, and the number of arms of the hydrophilic multi-arm polyethylene glycol is 3-12.

2. The composite material according to claim 1, wherein The composite material comprises 30 wt% to 95 wt% of a multi-arm amphiphilic block copolymer and 5 wt% to 70 wt% of an inorganic mineral; Preferably, the composite material comprises 50wt%-90wt% of the multi-arm amphiphilic block copolymer and 10wt%-50wt% of the inorganic mineral; Preferably, the molar ratio of the hydrophilic multi-arm polyethylene glycol segment to the lipophilic polyester segment is 1:4-8; Preferably, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate; Preferably, the hydrophilic multi-arm polyethylene glycol segment is derived from hydrophilic multi-arm polyethylene glycol, and the number of arms of the hydrophilic multi-arm polyethylene glycol is 4-8; Preferably, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol is 2000-200000 g / mol, preferably 10000-50000 g / mol.

3. The composite material according to claim 1 or 2, wherein: The oleophilic polyester chain segment is derived from an oleophilic polyester monomer; Preferably, the lipophilic polyester monomer is lactide; Preferably, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol segment is 2000-200000 g / mol, preferably 10000-50000 g / mol; Preferably, the number average molecular weight of the oleophilic polyester segment is 10,000-1,000,000 g / mol, preferably 90,000-250,000 g / mol.

4. The composite material according to any one of claims 1 to 3, wherein: The number average molecular weight of the multi-arm amphiphilic block copolymer is 12000-1200000 g / mol, preferably 100000-300000 g / mol; Preferably, the multi-arm amphiphilic block copolymer has a melt index of 1-50 g / 10 min, preferably 5-30 g / 10 min, at 190° C. and a load of 2.16 kg; Preferably, the composite material has an average pore size of 200-800 μm and a porosity of ≥40%.

5. A method for preparing a composite material, characterized in that: The method comprises the following steps: S1. In the presence of a catalyst, a hydrophilic multi-arm polyethylene glycol and a lipophilic polyester monomer are mixed to carry out a polymerization reaction to obtain a multi-arm amphiphilic block copolymer; S2, mixing and shaping the multi-arm amphiphilic block copolymer and the inorganic mineral to obtain the composite material; Wherein, the molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:160-10000.

6. The method according to claim 5, wherein: The molar ratio of the hydrophilic multi-arm polyethylene glycol to the lipophilic polyester monomer is 1:200-2000; Preferably, the catalyst is selected from at least one of stannous isooctanoate, stannous octoate, tributylaluminum and diethylzinc; Preferably, the amount of the catalyst is 0.1wt%-1wt% of the hydrophilic multi-arm polyethylene glycol, preferably 0.2wt%-0.6wt%; Preferably, the polymerization reaction conditions include: reaction temperature of 100-200° C., preferably 120-160° C.; reaction time of 3-6 h, preferably 4-5 h.

7. The method according to claim 5 or 6, wherein: The number of arms of the hydrophilic multi-arm polyethylene glycol is 3-12, preferably 4-8; Preferably, the number average molecular weight of the hydrophilic multi-arm polyethylene glycol is 2000-200000 g / mol, preferably 10000-50000 g / mol; Preferably, the lipophilic polyester monomer is lactide.

8. The method according to any one of claims 5 to 7, wherein: In step S1, the catalyst content in the multi-arm amphiphilic block copolymer is no more than 150 ppm in terms of metal; Preferably, based on the weight of the composite material, the mass fraction of the inorganic mineral is 5wt%-70wt%, preferably 10wt%-50wt%; Preferably, the inorganic mineral is selected from at least one of calcium phosphate, hydroxyapatite, bioglass and calcium carbonate; Preferably, the forming method is electrospinning and / or 3D printing.

9. A composite material prepared by the method according to any one of claims 5 to 8.

10. Use of the composite material according to any one of claims 1 to 4 and 9 in bone tissue repair.